2005
DOI: 10.1523/jneurosci.5301-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of Orbitofrontal Cortex Impair Rats' Differential Outcome Expectancy Learning But Not Conditioned Stimulus-Potentiated Feeding

Abstract: Patients with damage to the orbitofrontal cortex (OFC) display various impairments in cognitive and affective function, including a reduced ability to use information about the consequences of their actions to guide their behavior. In this study, rats with neurotoxic lesions of the OFC failed to use specific expectancies about outcomes to guide their learning of an instrumental discrimination task. In contrast, lesioned rats were unimpaired in a measure of learned motivational function, the potentiation of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
76
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 42 publications
12
76
2
Order By: Relevance
“…Rats that were previously fed these pellets in the conditioning context under food-deprivation (paired group) consumed significantly more food pellets than the rats that were never fed in the context (the unpaired group) [F(1,20) = 5.013, p < 0.04]). This finding is consistent with previous studies that showed CS-potentiated food consumption with explicit CSs [2][3][4][5][6][7]. In the second test, rats were presented with a familiar food different from the training pellets, standard lab chow.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Rats that were previously fed these pellets in the conditioning context under food-deprivation (paired group) consumed significantly more food pellets than the rats that were never fed in the context (the unpaired group) [F(1,20) = 5.013, p < 0.04]). This finding is consistent with previous studies that showed CS-potentiated food consumption with explicit CSs [2][3][4][5][6][7]. In the second test, rats were presented with a familiar food different from the training pellets, standard lab chow.…”
Section: Resultssupporting
confidence: 91%
“…For example, an auditory or visual conditioned stimulus (CS) that is paired with a food unconditioned stimulus (US) when rats are food-deprived will stimulate eating when they are food-sated [2]. A number of recent studies identified components of brain circuitry critical to the occurrence of this cue-potentiated eating [3][4][5][6][7]. However, those studies used a single training protocol, and only evaluated consumption of the food used as the US.…”
mentioning
confidence: 99%
“…Similarly, Mc-Dannald et al (2005) examined their data prior to the delivery of the first outcome, and these preoutcome data were similar to those from the entire stimulus duration (there was a DOE effect in shams, but not in rats with OFC lesions). Both of these measures demonstrated that without the direct experience of the outcome, sham animals display the DOE to the S D alone, whereas animals with lesions to either the BLA or OFC do not (see Figure 3 of Blundell et al, 2001, and Figure 4 of McDannald et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…BLA lesions impair performance on appetitive Pavlovian second-order conditioning, reinforcer devaluation (Hatfield, Jan, Conley, Gallagher, & Holland, 1996), conditional discrimination involving the DOE, and reward-specific Pavlovian-to-instrumental transfer (Blundell et al, 2001). The OFC is a cortical region with extensive connections to the BLA as well as other cortical and subcortical regions (hippocampus, basal ganglia, and thalamic nuclei) that may act as the goal-directed correlate of reward expectancy in the presence of a discriminative stimulus (Barbas, 2000;Cardinal et al, 2002;McDannald, Saddoris, Gallagher, & Holland, 2005;Pickens, Saddoris, Gallagher, & Holland, 2004;Schoenbaum, Setlow, Saddoris, & Gallagher, 2003). More specifically, it has been inferred that the OFC specializes in processing features essential for the guidance of behavior based on outcome expectancies (Schoenbaum, Chiba, & Gallagher, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation